Autophagy Regulation and Photodynamic Therapy: Insights to Improve Outcomes of Cancer Treatment - Martins, Waleska K.; Belotto, Renata; Silva, Maryana N.; Grasso, Daniel; Suriani, Maynne D.; Lavor, Tayná S.; Itri, Rosangela; Baptista, Mauricio S.; Tsubone, Tayana M. (Frontiers in Oncology, 2021)
Cancer is an age-related disease that over the next 10 years will become the most prevalent health problem worldwide. Although cancer therapy has considerably improved in the last decades, novel treatment concepts are highly needed to defeat this disease. Photodynamic Therapy (PDT) highlights a promising avenue to cure and manage several types of cancer. Over the past three decades, new light sources and photosensitizers (PS) have been developed to be applied in PDT, however, there is a lack of knowledge considering the main biochemical pathways needed to specifically trigger regulated cell death mechanisms, making it difficult to develop comprehensive improvements in PDT. Although autophagy modulation is raising as an interesting strategy to be used in cancer therapy, the main aspects regarding the role of autophagy in cell succumbing PDT-photoinduced damage remain elusive. Several reports highlight cytoprotective autophagy, as an ultimate attempt of cells to cope with the photo-induced stress and to survive. Moreover, other underlying molecular mechanisms that evoke PDT-resistance of tumor cells were considered. We review the paradigm about the PDT-regulated cell death mechanisms that involve autophagic impairment or boosted activation. When discussing the autophagy-targeted PDT-protocols to treat cancer, we underline those that alleviate or augment PDT-resistance of tumor cells. Thereby, this review provides insights into the mechanisms by which PDT can be used to modulate autophagy and emphasizing how this field represents a promising therapeutic strategy for cancer treatment.